Growing the Volunteer Pool: Identifying Non-Volunteers Most Likely to Volunteer - Lockstone-Binney, L.; Holmes, Kirsten; Meijs, L.C.P.M.; Oppenheimer, M.; Haski-Leventhal, D.; Taplin, Ross (SPRINGER, 2022)
There are ongoing management and societal challenges affecting volunteering participation. These place a premium on organizations identifying individuals that currently do not volunteer but have the willingness and capacity to do so, the “Potentials”. Supplementing the limited non-volunteer literature, we seek to quantify this potential volunteer pool using constructs aligned to the willingness, capability and availability dimensions from Meijs et al.’s (Volunt Action 8:36–54, 2006) volunteerability framework. Using binary logistic regression testing with a nationally representative sample of Australian volunteers and non-volunteers, we found partial support for the framework’s willingness and capability dimensions determining volunteer status. We then applied a predictive equation to the non-volunteer sample to calculate their percentage likelihood of volunteering, to identify a cohort of “Potential” volunteers. Further testing revealed statistically significant differences between this cohort compared to other non-volunteers based on various interventions for promoting volunteering. The implications of our novel study and an associated research agenda are discussed.